Gender-Specific Association of ATP2B1 Variants with Susceptibility to Essential Hypertension in the Han Chinese Population. (11th January 2016) - Xu, Jin; Qian, Hai-xia; Hu, Su-pei; Liu, Li-ya; Zhou, Mi; Feng, Mei; Su, Jia; Ji, Lin-dan
Abstract : Previous genome-wide association studies (GWASs) found that several ATP2B1 variants are associated with essential hypertension (EHT). But the "genome-wide significant" ATP2B1 SNPs (rs2681472, rs2681492, rs17249754, and rs1105378) are in strong linkage disequilibrium (LD) and are located in the same LD block in Chinese populations. We asked whether there are other SNPs within the ATP2B1 gene associated with susceptibility to EHT in the Han Chinese population. Therefore, we performed a case-control study to investigate the association of seven tagSNPs within the ATP2B1 gene and EHT in the Han Chinese population, and we then analyzed the interaction among different SNPs and nongenetic risk factors for EHT. A total of 902 essential hypertensive cases and 902 normotensive controls were involved in the study. All 7 tagSNPs within the ATP2B1 gene were retrieved from HapMap, and genotyping was performed using the Tm-shift genotyping method. Chi-squared test, logistic regression, and propensity score analysis showed that rs17249754 was associated with EHT, particularly in females. The MDR analysis demonstrated that the interaction of rs2070759, rs17249754, TC, TG, and BMI increased the susceptibility to hypertension. Crossover analysis and stratified analysis indicated that BMI has a major effect on the development of hypertension, while ATP2B1 variants have a minor effect.